Proyeksi Kebutuhan Air Bersih Pada Rumah Sakit Bhayangkara Pontianak Polda Kalimantan Barat - Muliani Muliani; Fathmawati Fathmawati; Fara Chitra (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2026)
Hospitals are healthcare facilities that rely heavily on the availability of clean water to support various activities, both medical and non- medical. Insufficient clean water availability can lead to the risk of nosocomial infections, environmental pollution, and a decline in the quality of healthcare services. This study aims to describe the need for clean water at the Bhayangkara Hospital, Pontianak, West Kalimantan Regional Police, and project its needs until 2030 based on applicable standards. The research method used was descriptive with an observational approach. Primary data were collected through direct observation and interviews at the hospital. In contrast, secondary data were obtained through literature review and regulations such as Ministerial Regulation No. 7 of 2019, No. 40 of 2022, and No. 2 of 2023. Data analysis was conducted by calculating water needs based on the number of patients, staff, and hospital operational needs, then comparing them to quality standards and minimum clean water requirements. The results of the study indicate that the demand for clean water in hospitals has been increasing annually, corresponding with the growth in patient numbers and the planned expansion of service facilities. Clean water needs by 2030 are estimated to reach 73,619 m3/day, with peak demand reaching 17,668 m3/hour. Based on these projections, hospitals require a reservoir with a minimum capacity of 303 m³ to ensure continuity of services during emergencies. This study concludes that hospitals must design their clean water management sustainably. Regular evaluation and improvement of the clean water distribution system are necessary to ensure optimal hospital service quality and meet environmental health standards.